A QUANTITIES METHOD OF INDUCTION MOTOR UNDER UNBALANCED VOLTAGE CONDITIONS - Ayong Hiendro (Universitas Ahmad Dahlan, 2010)
The most complete definition for the voltage unbalance is using complex voltage unbalance factor (CVUF) that consists of its magnitude and angle. Unfortunately, the definition did not distinguish between undervoltage and overvoltage unbalance conditions. In this paper, the analysis of the motor is performed using the method of symmetrical component and MATLAB software is used to investigate the performance of induction motor. The simulation results show that the International Electrotechnical Commission (IEC) definition of the voltage unbalance can be applied to evaluate total copper losses precisely. However, the phase angle of unbalance factor must be included for accurate predicting of peak currents and peak copper losses of the phase windings of the motor.The unbalanced conditions which distinguish between under and over voltage unbalance must also be taken into consideration for assessing all the quatities.